2021
DOI: 10.3390/biomedicines9020122
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment and Antithrombotic Strategies in Antiphospholipid Antibody Carriers

Abstract: Antiphospholipid antibodies (aPL) are a cluster of autoantibodies directed against plasma proteins with affinity for membrane phospholipids. The most frequently tested aPL are lupus anticoagulant (LA), anti-cardiolipin antibodies (aCL), and anti-β2-glycoprotein I antibodies (anti-β2GPI). aPL play a key pathogenic role in the development of the antiphospholipid syndrome (APS), a systemic autoimmune disease characterized by recurrent thrombotic and/or pregnancy complications in patients with persistent aPL. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…High titers of antibodies are considered to be more associated with clinical events in APS, as well as in specific AIDs 63,64 and increasing titers of autoantibodies are associated with a higher likelihood of having the disease. [64][65][66] In this study, we demonstrated that higher titers of aPS/PT IgG and IgM were associated with higher LR for TAPS.…”
Section: Discussionmentioning
confidence: 99%
“…High titers of antibodies are considered to be more associated with clinical events in APS, as well as in specific AIDs 63,64 and increasing titers of autoantibodies are associated with a higher likelihood of having the disease. [64][65][66] In this study, we demonstrated that higher titers of aPS/PT IgG and IgM were associated with higher LR for TAPS.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 In contrast, high levels of aPL strongly predict future thrombosis with and without underlying autoimmune diseases. 31,32 Consequently, we hypothesized that single IgA-positive individuals may be less likely to develop APS than dual- or triple-positive individuals. IgA-positive individuals can be classified into two categories: first, multiple aPL-positive group, whereby IgA coexists with IgM/IgG antibodies and can be identified with the conventional aPL assays; second, isolated IgA-positive group with a low risk of APS due to the low levels of antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a specific positivity for aPL, the number of aPL positive tests (single, double, or triple positivity), and the titer and isotype of aPL may all influence the risk of thrombosis development. 17 In particular, it has been reported that triple positivity is strongly correlated with the thrombotic risk. 18 We found that of the 53 women included, five women tested positive for aPL and we have three cases with isolated LAC, one case with isolated IgG aCL and one case with triple positivity (LAC, aCL IgM, aβ2GPI IgM).…”
Section: Discussionmentioning
confidence: 99%
“…Several pieces of evidence suggest that the aPL profile is linked to thrombotic risk. Indeed, a specific positivity for aPL, the number of aPL positive tests (single, double, or triple positivity), and the titer and isotype of aPL may all influence the risk of thrombosis development 17 . In particular, it has been reported that triple positivity is strongly correlated with the thrombotic risk 18 .…”
Section: Discussionmentioning
confidence: 99%